Advancing Equity Planning Now - Bates, Lisa K.; Hexter, Kathryn Wertheim; Krumholz, Norman; Project Muse. (Cornell University Press, 2018)
"Written by planning researchers and practitioners, this book is a resource for those interested in shaping public policy and the built environment for the benefit of all"--
Growth without displacement : a test for equity planning in Portland / Lisa K. Bates -- The evolution of the community development industry : a practitioner's perspective / Mark McDermott -- Economic diversity in low-status communities / Majora Carter -- Can we talk? : conversation, collaboration, and conflict for a just metro / Chris Benner and Manuel Paster -- Equity planning in a fragmented suburban setting : the case of St. Louis / Todd Swanstrom -- On the way there but not there yet : making accessibility the core of equity planning in transportation / Joe Grengs -- The opportunity challenge : jobs and economic development / Robert Giloth -- Equity policy and practice at the federal level : HUD's rental assistance demonstration / Patrick Costigan -- Planning for aging : addressing issues of equity / Deborah Howe -- The future of equity planning education in the United States / Ken Reardon and John Forester -- Public participation geographic information systems : a model of citizen science to promote equitable public engagement / Michelle M. Thompson and Brittany N. Arcenaux -- Conclusion : the future of equity planning practice / Norman Krumholz and Kathryn Wertheim Hexter.
Papers originally presented at a conference held in November 2015 at the Levin College of Urban Affairs, Cleveland State University.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social justice -- United States -- Congresses; Urban policy -- United States -- Congresses; Regional planning -- United States -- Congresses; City planning -- United States -- Congresses; Electronic books